Role of aetiology in the progression, regression, and parenchymal remodelling of liver disease: implications for liver biopsy interpretation. Issue 7 (28th April 2016) - Quaglia, Alberto; Alves, Venancio A; Balabaud, Charles; Bhathal, Prithi S; Bioulac‐Sage, Paulette; Crawford, James M; Dhillon, Amar P; Ferrell, Linda; Guido, Maria; Hytiroglou, Prodromos; Nakanuma, Yasuni; Paradis, Valerie; et al.
Abstract : Clinicopathological concepts on acute and chronic liver disease have evolved rapidly during the last few years, with advances in general and specific treatment options and improved patient outcomes. The old paradigm of 'irreversibility' of cirrhosis had been challenged in major ways, and the validity of the usage of the term 'cirrhosis' has come into question. This paper addresses aetiology‐based clinicopathological concepts and features that may deserve attention because they may determine disease outcome and, specifically, patterns of regression and remodelling. A variety of therapeutic interventions may influence remaining disease features after elimination of damaging agents (virus, alcohol, etc.), and determine the final clinical outcome including the risk of hepatocellular carcinoma (HCC). New concepts create new responsibilities and opportunities for the pathologist to contribute to the understanding of liver pathology and communicate this with clinical colleagues and researchers.